Increasing Vocabulary of Elementary Students Through Quizizz - Zulkifli, Zulkifli; Usman; Jamiluddin (FKDP (Forum Komunikasi Dosen Peneliti), 2025)
This study aims to improve the vocabulary mastery of sixth grade students at SDN 4 Banawa through the use of Quizizz. The research method used is classroom action research (CAR) which was carried out in two cycles. Each cycle consists of the stages of planning, action, observation, and reflection. The research instruments used were observation and test. The results of the research show a significant increase in student vocabulary, with the success rate increasing from 21% in cycle 1 to 89.5% in cycle 2. It passed the indicator of success which was 70%. These findings indicate that the use of Quizizz is able to create an interesting learning atmosphere, increase student motivation, and facilitate understanding of the material. The implication of this research is the importance of technology integration in learning, especially at the elementary school level. Keyword: Vocabulary Mastery, Gamified Learning, Quizizz, Classroom Action Research